Employment arrangements and well-being of migrant live-in care workers: Evidence from a study of Polish live-ins in Berlin - Lena Hipp; Sandra Leumann; Ulrich Kohler (sozialpolitik.ch, 2024)
This paper is the first to provide generalizable estimates on the economic and subjective well-being of 24-hour migrant care workers (“live-ins”) by type of work arrangement. In our empirical analyses, we draw on data from a survey on Polish live-ins working in Berlin selected via respondent-driven sampling (N=222), which allow us to compare live-ins who are contracted by care agencies with live-ins in other types of employment. The analyses show considerable differences in various outcomes between agency live-ins and nonagency live-ins. Compared to agency live-ins, nonagency live-ins are more likely to earn higher wages than agency live-ins but are more likely to report having less time to rest. It is therefore not surprising that we also find variation between agency and nonagency live-ins on different satisfaction outcomes. These findings have major implications for the regulation of migrant live-in care workers' employment.
Keywords: 320; migrant care work; live-ins; care agencies; working condition; respondent-driven sampling (RDS)